PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PPKn KELAS III SD NEGERI 064971 MEDAN TEMBUNG TAHUN PEMBELAJARAN 2024/2025 - Inneke M.F Togatorop; Indah Pratiwi; Atti Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to identify differences in PPKn learning outcomes for class III elementary school students at SD Negeri 064971 Medan Tembung, which are taught using the Problem Based Learning model. The type of research used is meta-analysis of previous studies. This research applies quantitative synthesis methods. The main objective is to evaluate the effect of using the Problem Based Learning model on Civics subjects at elementary school level. To overcome this, the author applies a problem-based learning model (Problem Based Learning) with the aim of improving student learning outcomes. This research is classroom action research involving class III students at SD Negeri 064971 Medan Tembung as subjects. The research results showed that there was an increase in student learning outcomes in Civics subjects and they met the minimum completeness criteria (KKM) set by the school, namely 65. In the initial stage, only 4 students or 31% achieved completeness with an average score of 77.5. In cycle I, the number of students who completed increased to 6 people or 46% with an average score of 80. In cycle III, 11 students or 85% achieved completion with an average score of 88.18. The action was stopped in cycle II because the success criteria had been achieved. From this research, it can be concluded that the application of the problem-based learning model has succeeded in improving PPKN learning outcomes for class III students at SD Negeri 064971 Medan Tembung.